Humanizing the algorithm: the effects of anthropomorphic framing and narrative perspective on attitudes toward artificial intelligence in autonomous vehicles - Lin, ShengJun (Nanyang Technological University, 2024)
Artificial intelligence (AI) has received varied portrayals in the media – either anthropomorphically framed as human-like entities, or non-anthropomorphically framed as futuristic machines. This study aims to examine the use of anthropomorphic framing in the communication of AI-automated technologies, and how different portrayals of AI may result in different public attitudes towards AI. Many instances of anthropomorphic framing in the media utilize first-person pronouns for the AI. By comparing the application of third-person and first-person pronouns, this study also aims to examine the effects of different narrative perspectives on attitudes towards AI, as well as how these different perspectives might interact with the use of anthropomorphic framing. An online experiment was conducted to test the proposed hypotheses. The results showed that anthropomorphic framing elicited more favorable attitudes towards AI compared with non-anthropomorphic framing, and that this effect was mediated by perceived uncertainty, perceived group membership, social presence, and trust. The first-person narrative perspective also resulted in higher social presence compared with the third-person narrative. The use of different narrative perspectives was found to interact with the use of anthropomorphic framing, such that anthropomorphic framing had a greater effect on the variables in the third-person condition. By understanding how the use of different framing methods and narrative perspectives might shape public attitudes towards AI, this study contributes theoretically to the understanding of communication, and help to improve communication efforts regarding AI.